(0 2 0)-Textured tungsten trioxide nanostructure with enhanced photoelectrochemical activity - Han, Hyun Soo; Park, Woosung; Hwang, Sung Won; Kim, Hyunkyu; Sim, Yelyn; Surendran, Subramani; Sim, Uk; Cho, In Sun (Journal of Catalysis, 2020)
Texturing, i.e., preferentially oriented deposition of a film with a specific crystallographic direction, enables the manipulation of the charge transport properties and surface reactivity of photoelectrodes for solar water-splitting. The advancement of solar water-splitting systems under neutral conditions is a vital strategy to reduce the economic and ecological traits of the prevailing strong acid or alkaline-based solar water-splitting systems. However, the photoelectrodes have to endure cumulative barriers in neutral media to convalesce the performance of the neutral solar water-splitting system. The implication of texturing in materials enforces the synergistic effect that is essential to confine the barriers to improve the performance of the photoelectrodes in eco-friendly neutral pH conditions. Here, we synthesized tungsten trioxide (WO3) films to achieve a columnar-type nanostructure with (0 2 0) texture, through a laser ablation deposition. Specifically, we modulated both deposition temperature and working pressure, enabling the (0 2 0) textured deposition of films, as well as the fine-tuning of the surface morphology. With optimized fabrication conditions, the (0 2 0)-textured WO3 film (thickness: 3.6 µm) showed improved photoelectrochemical water-oxidation performance, and the photocurrent density was ~3 mA/cm2 at 1.23 V versus reversible hydrogen electrode in an economic and ecological neutral condition. The WO3 films were further characterized using various methods, namely a UV–Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and Hall Effect measurements. Based on the measured film characteristics, we attributed enhanced charge transport and transfer characteristics to the (0 2 0)-texturing, and the formation of the optimal amount of oxygen vacancies.
Keywords: Crystallographic directions; Deposition temperatures; Hall effect measurement; Laser ablation deposition; Photoelectrochemical water oxidation; Photoelectrochemicals; Reversible hydrogen electrodes; Transfer characteristics; (0 2 0)-texture; Laser ablation deposition; Nanostructure; Photoelectrochemical water-splitting; WO3